MEMBACA PERSEPSI, MENCERMATI KOMUNIKASI, MEMPREDIKSI HUBUNGAN ANTARUMAT ISLAM DAN HINDU DI KOTA MATARAM, PROVINSI NTB - Kadri Kadri (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2020)
This study aims to unveil three fundamental things, namely perception, communication pattern and the prospect of interreligious relation mainly between Islam and Hindu in the city of Mataram, the capital of NTB (West Nusa Tenggara Province). This qualitative phenomenological study involved 25 participants from both religions. The data, garnered from interview, observation and documentation, were analyzed using Van Kaam’s phenomenological data analysis. The empirical evidence showed that the adherents of Islam and Hindu in the capital city of Mataram positively perceived each other without any negative remarks or stereotyping between them. This affirmative perception accorded with their friendly interreligious communication that took place in public sphere. This was depicted by the presence of two patterns of communications, i.e. active communication pattern, a permanent and direct relation associated to strong emotional bound; and passive communication pattern, which was situational with pragmatism nuance. The positive perception and communicative encounters across the two religious adherents indicated the harmonious relation between them, which simultaneously and perpetually consolidated the harmonious relation in the future between the religious believers of the two major religions in the city of Mataram.